An initial experience with an Extraluminal EZ‐Blocker®: A new alternative for 1‐lung ventilation in pediatric patients. Issue 4 (11th February 2018) - Templeton, Thomas Wesley; Templeton, Leah B.; Lawrence, Ann E.; Sieren, Leah M.; Downard, Martina G.; Ririe, Douglas G.
Summary: Background: The need for 1‐lung ventilation in school age, pediatric patients is uncommon and as a result there are relatively few devices available to facilitate lung isolation in this population. Furthermore, little is known about the efficacy and techniques of placement of the currently available devices. One of the newest devices available that may be appropriate in this age group is the EZ‐Blocker. Aims: We aimed to examine our initial experience with the EZ‐Blocker to evaluate the performance of this device with respect to potential improvements in technique and patient selection going forward. Methods: We performed a retrospective chart review of all pediatric patients who underwent 1‐lung ventilation with an EZ‐Blocker since the blocker became available at our institution. We recorded demographics, details of placement, intraoperative course, number of repositions, and any postoperative morbidity related to blocker placement or 1‐lung ventilation. Results: We were able to correctly place the EZ‐Blocker and achieve lung isolation in 8 of 11 patients. There was a single episode of repositioning required during 1‐lung ventilation with an EZ‐Blocker. Conclusion: The EZ‐Blocker was successful in providing lung isolation for a majority of our school age patients. Size constraints in children <6 years of age, excessive secretions, and distortions of tracheal anatomy seemed to be the greatest hindrances to successful placement and positioning of the device. Once correctly positioned, however, the EZ‐Blocker may be more stable than the Arndt endobronchial blocker.